Pathogenic mechanisms and the potential clinical value of circFoxo3 in cancers - Lei Zhang; Yin Wang; Yuan Zhang; Yanfang Zhao; Peifeng Li (Elsevier, 2021)
Circular RNAs (circRNAs) are covalently closed circular structures that can function in various physiological and pathological processes by acting as microRNA (miRNA) sponges, RNA-binding protein (RBP) sponges, mRNA transcriptional regulators, and protein translational templates. circFoxo3 is one of the most studied circRNAs and is generated from the tumor suppressor gene Foxo3. Increasing studies have demonstrated the multiple functions of circFoxo3 in the pathogenesis of different cancer types. circFoxo3 plays important roles in cancer development mainly by binding to various miRNAs. The diagnostic potential of circFoxo3 has been revealed in several cancers. Some research results have been found to contradict the results of other studies, and this may be due to insufficient sample sizes and inconsistencies in the experimental and nomenclature methods. In this review, we systematically summarize current knowledge about the biogenesis and functions of circRNAs, elucidate the roles of circFoxo3 in different cancers, and explore the clinical applications of circFoxo3.